The Effect of Teacher's Digital Literacy Level on the Quality of Online Learning at Adiwerna Vocational School, Tegal (Indonesian Journal of Curriculum and Educational Technology Studies, 2021)
This study aims to reveal the relationship between teachers' digital literacy skills and the quality of online learning in schools. This research uses a quantitative approach with the type of correlation research. The researchers used a teacher digital literacy scale and online learning quality scale instruments to gather the data from 64 teachers as the sample of this research. The reliability of variable X is 0.750 and variable Y is 0.837. Next, the analysis of the data uses simple regression and product moment. The result of the research showed that (1) teachers’ digital literacy level at SMK N 2 Adiwerna is good in the category at 80,56% with an average score of 97.08, (2) in line with the previous finding, the quality of online learning also has a good result at 77.85% with an average score of 101.98, and (3) there is a relation between the level of teachers’ digital literacy and the quality of online learning, in detail the level of teachers’ digital literacy has a positive effect on the quality of online learning at SMK Negeri 2 Adiwerna. Abstrak Penelitian ini bertujuan mengungkapkan hubungan antara kemampuan literasi digital guru dengan kualitas pembelajaran daring di Sekolah. Metode penelitian menggunakan pendekatan kuantitatif dengan tipe penelitian korelasi. Sampel dalam penelitian ini adalah seluruh guru pengajar sejumlah 64 guru. Pengumpulan data melalui instrumen skala literasi digital guru dan skala kualitas pembelajaran daring. Dengan reliabel variabel X sebesar 0,750 dan variabel Y sebesar 0.837. Analisis data dilakukan dengan regresi sederhana dan product moment. Hasil penelitian menunjukkan: 1) Tingkat literasi digital guru di SMK Negeri 2 Adiwerna termasuk dalam kategori baik dengan perolehan scor 80,56% dari 100% dengan skor rerata 97,08, 2) Kualitas pembelajaran daring di SMK Negeri 2 Adiwerna termasuk dalam kategori baik dengan perolehan skor 77,85% dengan skor rerata 101,98, 3) Terdapat hubungan antara tingkat literasi digital guru dan kualitas pembelajaran daring di SMK Negeri 2 Adiwerna, bahwa tingkat literasi digital berpengaruh positif terhadap kualitas pembelajaran daring di SMK negeri 2 Adiwerna.